Age-Related Differences in Functional Nodes of the Brain Cortex – A High Model Order Group ICA Study - Littow, Harri; Abou Elseoud, Ahmed; Haapea, Marianne; Isohanni, Matti; Moilanen, Irma; Mankinen, Katariina; Nikkinen, Juha; Rahko, Jukka; Rantala, Heikki; Remes, Jukka; Starck, Tuomo; Tervonen, Osmo; et al. (Frontiers in Systems Neuroscience, 2010)
Functional MRI measured with blood oxygen dependent (BOLD) contrast in the absence of intermittent tasks reflects spontaneous activity of so called resting state networks (RSN) of the brain. Group level independent component analysis (ICA) of BOLD data can separate the human brain cortex into 42 independent RSNs. In this study we evaluated age related effects from primary motor and sensory, and, higher level control RSNs. 168 healthy subjects were scanned and divided into three groups: 55 adolescents (ADO, 13.2 ± 2.4 yrs), 59 young adults (YA, 22.2 ± 0.6yrs) , and 54 older adults (OA, 42.7 ± 0.5 yrs), all with normal IQ. High model order group probabilistic ICA components (70) were calculated and dual regression analysis was used to compare 21 RSN’s spatial differences between groups. The power spectra were derived from individual ICA mixing matrix time series of the group analyses for frequency domain analysis. We show that primary sensory and motor networks tend to alter more in younger age groups, whereas associative and higher level cognitive networks consolidate and re-arrange until older adulthood. The change has a common trend: both spatial extent and the low frequency power of the RSN’s reduce with increasing age. We interpret these result as a sign of normal pruning via focusing of activity to less distributed local hubs.